Vertical dynamics of free-living and particle-associated vibrio communities in the eastern tropical Indian Ocean - Zhu, Shaodong; Wang, Xiaolei; Zhao, Wenbin; Zhang, Yulin; Song, Derui; Cheng, Haojin; Zhang, Xiao-Hua (Frontiers in Microbiology, 2023)
Members of the family Vibrionaceae (vibrios) are widely distributed in estuarine, offshore, and marginal seas and perform an important ecological role in the marine organic carbon cycle. Nevertheless, there is little knowledge about whether vibrios play ecological roles in the oligotrophic pelagic area, which occupies a larger water volume. In this study, we investigated the abundance, diversity, and composition of free-living and particle-associated vibrios and their relationships with environmental factors along the water depth in the eastern tropical Indian Ocean (ETIO). The abundance of vibrios in free-living fractions was significantly higher than that of particle-associated fractions on the surface. Still, both were similar at the bottom, indicating that vibrios may shift from free-living lifestyles on the surface to mixed lifestyles at the bottom. Vibrio-specific 16S rRNA gene amplicon sequencing revealed that Paraphotobacterium marinum and Vibrio rotiferianus were dominant species in the water column, and Vibrio parahaemolyticus (a clinically important pathogen) was recorded in 102 samples of 111 seawater samples in 10 sites, which showed significant difference from the marginal seas. The community composition also shifted, corresponding to different depths in the water column. Paraphotobacterium marinum decreased with depth, and V. rotiferianus OTU1528 was mainly distributed in deeper water, which significantly correlated with the alteration of environmental factors (e.g., temperature, salinity, and dissolved oxygen). In addition to temperature and salinity, dissolved oxygen (DO) was an important factor that affected the composition and abundance of Vibrio communities in the ETIO. Our study revealed the vertical dynamics and preferential lifestyles of vibrios in the ETIO, helping to fill a knowledge gap on their ecological distribution in oligotrophic pelagic areas and fully understanding the response of vibrios in a global warming environment.